Improved eight-process model of precast component production scheduling considering resource constraints - Ruan, Minhao; Xu, Feng (Journal of Civil Engineering and Management, 2022)
Reasonable production scheduling plays a vital role in the production of precast component factories. However, previous static scheduling models no longer fit actual production. In particular, some factors will cause errors in the actual delivery time of the components, including the lack or redundancy of processes in the model, resource constraints required by the core processes, and differences in transportation schemes. Moreover, the optimization goal of simply pursuing the minimization of fines from order delivery underestimates companies’ emphases on reputation. Therefore, this study proposes an improved model for precast component production scheduling considering resource constraints. The number of production processes is adjusted to eight, and three resource constraints for mold, steel, and concrete are added. An enterprise decision-making coefficient is introduced into the optimization object function, and the constraints of the transportation scheme are improved. Finally, a real case study is conducted to verify the applicability of the model. Compared with previous models, the developed model fills the gap in considering production resource constraints and enterprise decisions in precast production, can better meet diverse production conditions and business needs of factories for scheduling, and help give full play to the advantages of prefabricated construction.